Absorption behaviour of Pb(II) by Rhodotorula mucilaginosa. (May 2015) - Jiang, B. H.; He, H.; Zhao, Y.; Li, L.; Hu, X. M.
Abstract : In this work, a yeast strain Rhodotorula mucilaginosa WT6-5 that could grow at the pH from 3·0 to 8·0, isolated from tailings soil in Huludao of Liaoning province, China, was investigated with respect to lead ions in aqueous solutions. The effect of initial lead concentration on biosorption quantity is studied at 20, 30, 40 and 50°C, respectively. The experimental results are fitted to the Langmuir and Freundlich model isotherms to obtain the characteristic parameters of each model using non-linear regressive analysis. The maximum biosorption capacity of lead ions onto R. mucilaginosa WT6-5 is 12·1097 mg g −1 at 30°C. For the solution containing 10 mg L −1 Pb 2+ at pH 5·0, the maximum absorption rate is reached at 92·75%. The elements of R. mucilaginosa WT6-5 biomass before and after absorption were observed using X-ray fluorescence. The results indicated that Pb 2+ biosorption mechanism of R. mucilaginosa WT6-5 is a type of ions exchange and surface complexation.